Peran Dukungan Keluarga terhadap Praktik Pemberian ASI Eksklusif (Studi di Desa Ketapang Laok Kecamatan Ketapang Kabupaten Sampang Madura) - Istianah, Nine Zainiyatul; Masruroh, Nur; Lestari, Yanesti Nuravianda (Sport and Nutrition Journal, 2020)
Directly breastfeeding requires support from the nearest person, such as family members, friends, relatives, and co-workers. The greater the support gained for breastfeeding the greater the ability to survive for breastfeeding. The purpose of this study was to determine the relationship of family support level with exclusive breastfeeding in Ketapang Laok Village, Ketapang District, Sampang Madura District. The type of this study is analytical with a case-control approach, the population is all breastfeeding mothers who have babies aged â‰¥ 6 months in the village of Ketapang Laok as many as 242 people. A sample of 170 respondents of breastfeeding mothers with infants aged â‰¥ 6 months was taken by cluster random sampling. The independent variable is the level of family support and the dependent variable is exclusive breastfeeding. The data were collected through a questionnaire and then analyzed using a Chi-Square test. The results showed that 85 breastfeeding mothers (case group) mostly (57.1%) received good family support and nearly half (33.3%) received less family support. Then from the control group, nearly half (42.9%) received good family support, and most (66.7%) received less family support. The result of the analysis using the Chi-Square test shows that Ï = 0,004 means there is a relationship between family support level with exclusive breastfeeding in Ketapang Laok Village Ketapang Subdistrict, Kabupaten Sampang Madura. There is a relationship between the level of family support and exclusive breastfeeding. Thus, the family is expected to provide support for the mother exclusively breastfeeding.